Projections in Indonesian Newspapers' Headlines - Nurmayana Nurmayana; Wiwien Pratiwi Harsa; Epi Supriyani Siregar (Edulitics (Education, Literature, and Linguistics) Journal, 2023)
People cannot attain a communicative goal unless their words address specific cultural or contextual challenges. Thus, language is viewed as a social tool to assist humans in conveying meaning; but, this meaning cannot be obtained if words are conveyed in isolation. As a result, we require contexts or settings in which more phrases and words can be placed in order for listeners or readers to comprehend the meaning behind utterances and words. By applying Halliday’s Systemic Functional Linguistics Theory, this study aims to observe one of three types of meanings, it was ideational meanings. It focuses on language which is used by people in both types of local and regional newspapers to convey information or messages about the experiences of the speakers. Each speaker used different clauses which contained dependent and independent clauses that we call clause complex. To analyze the aspect of projection; Hypotactic Locution, Paratactic Locution, Hypotactic Idea, Paratactic Idea, and Quasi-Projection which were used or appeared in Indonesian newspapers’ story texts. The significance of the study is to improve students’ linguistic knowledge and their writing skill by mastering text structures.